Segmentation, and the Indian Automobile Industry - Narain, Raghav (2006)
The automobile industry has been called an industry of industries and during these times, the Indian automobile industry is booming with a number of multi-national companies having entered and others poised to do the same. Indian manufacturers have also improved their products in order to survive in the face of global competition. With such a rapidly growing industry catering to the second largest population in the world, it becomes necessary to find some direction for focusing marketing efforts. The segmentation on the Indian automobile is still at an evolutionary stage and there is little literature on the subject. This dissertation will explore the concept of segmentation and visit the various methods suggested in the previous literature, it will engage in primary research in the Indian automobile industry and try to understand segmentation as it is practiced in this industry and suggest the most suitable methods depending on the findings. The purpose of this dissertation is not to provide empirical generalisations for segmentation, nor is it to try and negate any views provided in the previous literature. A qualitative approach has been taken to try and explore the segmentation concept in the automobile industry of India, and suggest certain other ways of doing so based on the research.